2010
DOI: 10.1007/s00011-010-0193-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of the CCR1 receptor in the inflammatory response to tobacco smoke in a mouse model

Abstract: ObjectiveThe aim was to create pathological changes in mice relevant to human smoke exposure that can be used to further understand the mechanisms and pathology of smoke-induced inflammatory disease.MethodsMice were exposed to tobacco smoke or lipopolysaccharide (LPS) to generate an inflammatory infiltrate within the lungs.ResultsTobacco smoke exposure over a 4 day period led to neutrophilia in the lungs of BALB/c mice. Within the inflammatory exudates, significant changes were also seen in protein levels of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Notably, CCR1 serves as a receptor for a number of inflammatory chemokines and is upregulated in response to inflammatory stimuli [18][19][20]. Studies showed that CCR1 was involved in the inflammatory response to cigarette smoking in murine models [21], and it may play a critical role in the pathogenesis of COPD. Similarly, Joubert et al demonstrated that CCR1 was expressed on human airway smooth muscle cells in patients [22], which may involve in airway remodeling in asthma.…”
Section: Aging Discussionmentioning
confidence: 99%
“…Notably, CCR1 serves as a receptor for a number of inflammatory chemokines and is upregulated in response to inflammatory stimuli [18][19][20]. Studies showed that CCR1 was involved in the inflammatory response to cigarette smoking in murine models [21], and it may play a critical role in the pathogenesis of COPD. Similarly, Joubert et al demonstrated that CCR1 was expressed on human airway smooth muscle cells in patients [22], which may involve in airway remodeling in asthma.…”
Section: Aging Discussionmentioning
confidence: 99%
“…Several groups, using knock-out and transgenic mice, have clearly demonstrated the importance of multiple genes and pathways, including chemokine/cytokine receptors (e.g. C–C motif receptor (CCR)1, CCR5, CCR6 [ 12 14 ]), metalloproteinase enzymes (e.g. MMP-9/12 [ 15 ]), cytokines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CS has been used extensively to investigate mechanisms of COPD pathogenesis since it is the major risk factor in the development of COPD [ 3 ]. While whole body exposure to CS for a short-term (3 days to 4 weeks) has been useful in evaluating the mechanisms of CS-induced acute lung inflammation and defective innate immune responses to subsequent infections [ 4 - 7 ], long-term exposure to CS for periods up to 6 months has been employed to understand the mechanisms of emphysema development [ 8 - 11 ]. However, neither of these models show changes in small airways, which plays a major role in the development of airflow limitation in COPD implying that other factors in addition to CS are required to mimic COPD lung disease in mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%